THE CHALLENGE OF TEACHING HUMANISTIC SOCIOLOGY HUMANISTICALLY AT A COMMUNITY COLLEGE - Brennecke, Jan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The teaching of humanistic sociology and the implementation of what might be called humanistic teaching strategies in the classroom are two different things. The former is the easier of the two to accomplish. The latter involves a quality of interaction between students and instructors as well as between and among students themselves that serves to empower students through development of their individuality, dignity, and autonomy. This involves, among other things, the development of critical thinking skills and can be done in any discipline. In the teaching of sociology, it includes assisting students to develop an understanding of the everyday taken-for-granted social world through the lens of sociology generally and the lens of humanistic sociology specifically.